PENGARUH POLA KEPEMIMPINAN KEPALA SEKOLAH DAN SUASANA KERJA TERHADAP KINERJA GURU AGAMA HINDU DI GUGUS PERKUTUT KECAMATAN NUSA PENIDA KABUPATEN KLUNGKUNG - Sujatindriasih, Ni Luh Putu (JAPAM (Jurnal Pendidikan Agama), 2025)
Education in Indonesia in general is still experiencing many problems, namely involving manyfactors related to education, including those related to the curriculum, management and educationpolicy. One of these problems is the low quality of education. This research aims to analyze theinfluence of school principals' leadership patterns and work atmosphere on the performance ofHindu religious teachers in Gugus Perkutut, Nusa Penida District, Klungkung Regency. Theresearch method used is a quantitative method with a survey approach, where data is collectedthrough questionnaires distributed to Hindu religious teachers in the area. The results of theresearch show that (1) Leadership patterns and work atmosphere have a positive and significanteffect on the performance of Hindu Religion teachers in the Perkutut Cluster, Nusa Penida District,Klungkung Regency. (2) Leadership patterns have a positive and significant effect on theperformance of Hindu Religion teachers in the Perkutut Cluster, Nusa Penida District, KlungkungRegency. (3) The work atmosphere has a positive and significant effect on the performance ofHindu religious teachers in the Perkutut Cluster, Nusa Penida District, Klungkung Regency. Thismeans that the better the working atmosphere, the performance of teachers in the Perkutut Cluster,Nusa Penida District, Klungkung Regency will increase. The implications of this research show thatparticipative school principal leadership patterns and a conducive working atmosphere are veryimportant to improve the performance of Hindu religious teachers in Gugus Perkutut, Nusa PenidaDistrict, Klungkung Regency.